FROM COLONIAL LEGACY TO MODERN INTELECTUAL PROPERTY REFORM: A COMPARATIVE STUDY OF INTELECTUA PROPERTY IN INDONESIA AND GEORGIA - I Gede Agus Kurniawan; Rafika Amalia; Maia Kapanadze (Kertha Semaya: Journal Ilmu Hukum, 2026)
This research presents a historical-comparative analysis of the development of intellectual property rights from ancient civilizations to modern IPR systems, and compares the legal approaches to IPR reform regulation in Indonesia and Georgia within a global context. The aim is to reveal the relationship between the historical roots of IPR, the transition from colonial systems to contemporary IPR orders, and the differences in legal policies in developing and transition countries with different geopolitical backgrounds. Research shows that IPR has deep historical roots, with forms of incentives and protection for inventions, artworks, and distinctive products known in ancient civilizations such as China, Greece, Egypt, India, and the Islamic world. These were the precursors to patents, trademarks, and copyrights, although they were still royal monopolies, not common rights of citizens, and only evolved into modern formal legal systems after the emergence of the Venetian Patent Law (1474), which became the basis for modern patents. In legal comparison, Indonesia and Georgia are both building IPR systems based on TRIPS, WIPO, and international conventions, with similar legal structures (separate laws, central authorities, a "first-to-file" system, and automatic copyright protection), but they differ in their backgrounds, agendas, and reform approaches. Indonesia integrates customary law, traditional knowledge, and cultural expressions into its IPR system, while Georgia takes a technocratic and international standards-based approach that prioritizes technical aspects and international markets. In terms of law enforcement, Indonesia faces limitations in capacity and inter-agency coordination, resulting in slow and uneven application of the law. The novelty of this research lies in the fact that the journey of IPR from informal forms of protection in ancient times to the modern IPR system reflects a shift from discriminatory and exclusive laws to a more open and standardized system. However, it still requires contextual adjustments to balance exclusive rights and social justice, and demonstrates that the direction of IPR reform in each country is determined not only by international norms, but also by unique historical backgrounds, political structures, and national development interests.